From Flanders to Portugal: A Portuguese Painter in Pursuit of Prestigious Flemish Painting—Materials and Techniques Compared Through an Analytical Approach - Vanessa Antunes; António Candeias; José Mirão; Sara Valadas; Ana Cardoso; Maria José Francisco; Alexandra Lauw; Marta Manso; Maria Luísa Carvalho (Heritage, 2025)
This study offers fresh insights into the technical and stylistic exchanges between Flemish and Portuguese panel painting during the late 15th and early 16th centuries. By comparing two contemporaneous works, we trace Flemish influence in Portugal through a detailed materials and techniques analysis. Non-invasive, in situ methods—including energy dispersive X-ray fluorescence (XRF), macro-photography (MP), infrared reflectography (IRR), and dendrochronology—were used to examine each painting’s wooden support, ground layer, underdrawing, and pigment stratigraphy. Select micro-sampling analyses—micro-Fourier-transform infrared spectroscopy (μ-FTIR), scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS), and micro-Raman spectroscopy (µ-Raman)—provided complementary data on binder and pigment composition. While both paintings share nearly identical pigments and layering sequences and employ comparable coating techniques, their ground compositions differ subtly. Notably, the Flemish work features extensive gold-leaf application, whereas underdrawing execution takes on principal importance in the Portuguese example. Together, these findings reveal that Jorge Afonso’s workshop developed a distinct Portuguese method—rooted in Flemish practices disseminated by Quentin Metsys—yet adapted to local materials and aesthetic priorities.